Occurrence of a nearctic Hyrnenoptera Eulophidae belonging to the genus Achrysocharoides (Hyrnenoptera Eulophidae) on Phyllonorycter robiniella (Clemens) in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The occurrence of a nearctic Hymenoptera Eulophidae belonging to the genus Achrysocharoides is reported. For the first time the parasitoid was collected in Italy from Phyllonorycter robiniella (Clemens) on Robinia pseudoacacia L. Presently, the collected specimens are ascribed to the species A. gahani Miller; however, the possibility that these specimens could belong to a new species, only strictly related to the previous one, is here discussed. Preliminary data on morphology and biology of this endoparasitoid are given. The report of this natural enemy of Ph. robiniella is new for both palaearctic and nearctic fauna and opens promising perspectives of biological control in the biocoenosis of black locust in Europe.
Keywords: Achrysocharoides gahani; Robinia pseudoacacia; leaf miners; biological